Tratamento de poluentes emergentes (Permanganato de potássio, furosemida, microplásticos PET e glitter) por processo de coagulação/ floculação/ sedimentação com uso de coagulante orgânico extraído das sementes de Moringa oleífera - Rios, Magali de La Cruz (2022)
Emerging Pollutants (PE) are natural or synthetic, organic or inorganic chemical substances with high toxic potential and adverse effects on the environment and uman health. These are marketed as hygiene products, pharmaceuticals (medicines), agrochemicals, packaging, among others. The control is not yet regulated by national or international entities. Also, its availability of removal methods is limited. Among the different types of emerging pollutants, those of pharmaceutical origin and particles such as microplastics stand out, as they are the ones that were most found in different aquatic ecosystems, thus making water purification treatments difficult, which generates an important concern regarding to its quality. One type of promising methodology for these emerging pollutants is removal by coagulation through a solution of Moringa oleifera seeds as a coagulant. The objective of this work was to evaluate the efficiency of the combination of two coagulation processes, flocculation and sedimentation and filtration using Moringa oleifera seeds as an organic coagulant for the treatment of synthetic water contaminated with emerging pollutants Microplastics Polyethylene terephthalate (PET), Glitter and permanganate potassium, furosemide and their interactions. This research was divided into 3 phases, the first phase being the removal of PET microplastic and glitter in masses of 0.3; 0.5 and 0.9 g using concentrations of 30, 60 and 90 mg.L-1 of saline organic coagulant extracted from Moringa oleífera (MO) seeds, where removal efficiencies of 89% and 96% were obtained, respectively. In the second phase, the removal efficiency of potassium permanganate was determined at concentrations of 1.92.10-4, 2.88.10-4 and 3.84.10-4 mol.L-1 and furosemide at concentrations of 0.1; 0.2; 0.3 mg.mL-1 and 32, 48 and 64 mg.L-1 of organic coagulant MO, obtaining results of 90% and 62%. The third phase was due to the efficiency of removing the interactions of potassium permanganate with polyethylene terephthalate microplastic, potassium permanganate with glitter microplastic, furosemide with polyethylene terephthalate microplastics, furosemide with glitter microplastics, where drug and microplastic concentrations were maintained and used constantly. 90 mg.L-1 of organic coagulant, the best results were 97 and 100%, 97 and 85%, 76 and 43%, 75 and 66%. The removal results were characterized through the calculation of the zeta potential, Fourier transform infrared spectroscopy, X-ray diffractometers and Scanning Electron Microscope. Concluding that the saline organic coagulant extracted from the seeds of Moringa oleífera is efficient in the removal of microplastic from Polyethylene terephthalate, glitter, potassium permanganate and furosemide.